2018
DOI: 10.4236/ojogas.2018.34023
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Method for the Accurate Determination of Chemical Oxygen Demand (COD) in High Chloride Oilfield Wastewater

Abstract: In this work, in order to find a method for the accurate determination of chemical oxygen demand (COD Cr) in high chloride oilfield wastewater, the interferences of chloridion (Cl −) on COD Cr determination were first studied based on the Chinese national standard GB 11914-89. The results showed that the COD Cr values and deviations determined by the classical potassium dichromate (K 2 Cr 2 O 7) method increased gradually with the increase of Cl − mass concentration in water samples. Then, theoretical and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…In chloride-rich oilfield wastewater, TOC was proposed as an alternate index for COD and studies reported an acceptable correlation between TOC and COD in oilfield wastewater (11) . A study by Zhang et al, reported the feasibility of dichromate method using low concentration oxidant for high chloride oilfield wastewater (29) . When COD determination on several wastewater was done with manganese (III) as oxidant and silver nitrate for chloride removal, a high correlation (R2 = 0.9935) to the standard method with a mean recovery rate of 78.1% (±5.2%) was reported (12) .…”
Section: Resultsmentioning
confidence: 99%
“…In chloride-rich oilfield wastewater, TOC was proposed as an alternate index for COD and studies reported an acceptable correlation between TOC and COD in oilfield wastewater (11) . A study by Zhang et al, reported the feasibility of dichromate method using low concentration oxidant for high chloride oilfield wastewater (29) . When COD determination on several wastewater was done with manganese (III) as oxidant and silver nitrate for chloride removal, a high correlation (R2 = 0.9935) to the standard method with a mean recovery rate of 78.1% (±5.2%) was reported (12) .…”
Section: Resultsmentioning
confidence: 99%
“…Metode uji COD berkembang mulai dari metode volumetri [4]- [8], spektrofotometri UV-Vis [3], [9]- [14], sensori [4], [5], [15], dan elektrokimia [16]. Metode standar yang digunakan dalam uji COD adalah metode refluks tertutup secara spektrofotometri UV-Vis yang mengacu pada SNI 6989.2:2019 [3].…”
Section: Pendahuluanunclassified
“…Mercuric sulfate has proven to treat the higher chloride content during COD determination [9,11]. The pre-treatment using this substance is considered successful, when wastewater has approximately 1,000-2,000 mg/L Cl- [8,9]. Although the chemical is considered toxic, but since it is still recommended by many governmental regulations and standards, not to mention much more practical, the procedure remains usable and accepted [10].…”
Section: Efforts To Overcome High Chloride Interferencementioning
confidence: 99%
“…Chemical used for this purpose is commonly mercuric sulfate (HgSO 4 ). However, for industries which have higher chloride content than 2,000 mg/L, such as typical industrial coffee factories that ranges 4,000-4,600 mg/L, and wastewater in oilfield that exceeds 120,000 mg/L, the capability of mercuric sulfate needs to be evaluated further [7,8]. Similarly at our wastewater sample, the chloride ion may reach up to 18,000 mg/L.…”
Section: Introductionmentioning
confidence: 99%